Dignity Of Nature: A Resignification Of Human Dignity - de Lima Barbosa, Ingrid (2021)
Today, the era of animal consciousness is proclaimed, that is, the overcoming of the speciesist and anthropocentric paradigm that places human beings above all species. Such a change of perspective begins with the resignification of human dignity to beyond human animals, giving it an ecological aspect. It is intended, therefore, to analyze the possibility of a linguistic opening of human dignity to the ecological bias of today and, thus, to advocate for the dignity of life, which goes beyond the human species. The dialectical method was used for the objective of presenting a new conception of reality, allied to the theoretical analytical and documental approach, of qualitative nature, along with the critical analysis of the interpretations attributed to the principle of human dignity, as well as the change of reality which today presents itself to scholars, with the utmost concern given to the environment as an end in itself. This scientific method was realized through the use of books, scientific articles, academic papers (Dissertations), a higher court decision and international documents. It was concluded that the constitutional and international reading of human dignity must accompany the new perceptions that emerge with the development of the study of environment and its components, without neglecting the possibility that nonhuman animals may hold rights before men.